Formulation of Transparent Solid Soap from Palm Kernel Oil - Andri Prasetiyo; Lungguk Hutagaol; Lidya Luziana (Jurnal Jamu Indonesia, 2020)
Palm kernel oil contains fatty acids, especially lauric acid at 46-52%. Lauric acid has the properties of hardening, cleaning, producing foam and softening that is needed in making soap. The purpose of this study is to make transparent solid soap from a combination of glycerin, sucrose, and ethanol 96% as a transparent agent that meets the requirements of quality tests and organoleptic tests. Made 9 (nine) formulas with some combination of glycerin, sucrose, ethanol 96% by a semi-boiled method that is mixing palm kernel oil and stearic acid which has been melted at 60˚C, then adding 30% NaOH, stirring at 70- 80˚C. Transparent agent and other additives are mixed into the soap mass obtained from the saponification process, then poured into a soap mold and carried out a curing process for 2 weeks. The result of this research is obtained a transparent yellow solid soap that is the bright and distinctive smell of coconut perfume with a pH of 8.35-8.64, the hardness of 21.30-38.13 10-1 mm, moisture content of 21.48-33.33%, free fatty acid content 0,88-0,96%, unsaturated fat content 1,45-2,38%, surface tension 27,93-32,34 dyne/cm. Transparent solid soap that meets the quality requirements and the organoleptic test is formula A with PH 8.64, hardness 25.80 10-1 mm, moisture content 25.55%, free fatty acids 0,94%, unsaturated fat 1,45%, surface tension 30.02 dyne/cm.